A Multimodal Measurement Method of Users' Emotional Experiences Shopping Online. Issue 5 (26th June 2014) - Guo, Fu; Cao, Yaqin; Ding, Yi; Liu, Weilin; Zhang, Xuefeng
Abstract Emotions play an important role in the design of e‐commerce websites. A website should satisfy its users' emotional needs. Emotion measurement is a prerequisite to understanding users' emotional needs; because emotions contain complicated components, they are difficulty to measure. To interpret users' emotional experiences while the users are interacting with e‐commerce websites, we propose a multimodal measurement method conjoint using questionnaires, eye tracking, and physiological measures. The effects of various websites on users' emotions and the relationship between users' subjective emotional ratings, eye movements, and physiological responses, along with the effects of their emotions on behavior intentions, were analyzed. The results indicate that differences in users' emotional experiences while shopping on various e‐commerce websites are primarily embodied in subjective emotional ratings and eye movements. There is a correlation between users' subjective emotional ratings, eye movements, and physiological responses, and to some extent, users' emotional experiences can affect their behavior intentions.